Characterization of class-switched B cells in chickens - von La Roche, Dominik; Schumacher, Magdalena; Kohn, Marina; Trapp, Johanna; Schusser, Benjamin; Rautenschlein, Silke; Härtle, Sonja (Frontiers in Immunology, 2024)
While B cell development in the birds’ primary B cell organ, the bursa Fabricius, is relatively well understood, very little is known about post bursal B cell differentiation into plasma and memory cells though these cells are essential for a protecting antibody response and so far, no specific markers for these cells were available. Since immunoglobulin class switch is one part of the B cell differentiation process, our objective was to conduct a first detailed investigation of class-switched chicken B cells. As only very few IgY and IgA expressing cells were detected in lymphoid organs of young chickens, we used CD40L and IL-10 to establish a prolonged in vitro culture system, which induces B cell proliferation, class switch to IgY and IgA and enhanced antibody secretion. This enabled a phenotypic analysis of differentiating B cells. Importantly, these cells lost surface expression of the B cell markers chB6 and BAFF-R. B cell receptor surface expression remained unchanged, showing that while differentiating toward plasma cells, B cells can be addressed by L chain staining. Newly generated potential plasma cell markers CD138 and TACI showed only a transient expression on cultured cells and rather act as markers for B cell activation than plasma/memory cells in general. CD57 upregulation was connected to activation and blast formation but not to class switch. We also examined potential changes in class-switched cells in different age groups and post vaccination. Surprisingly, bursa involution, laying and age had no distinct effects on the presence of class-switched cells, but we detected significantly more class-switched B cells post vaccination. Hence, we are now able to generate class-switched plasmablasts in vitro for a more detailed characterization and can address them under different conditions in chickens for further analysis of their B cell response.